D2 (diségno, 2022)
In recent decades, especially since the 1990s, the growing of training courses in the area of design has brought about an exceptional variety of design declinations.A sort of euphoric openness towards the most varied thematic areas, from product to service, from interiors to fashion and, of course, to communication, a discipline transversal to multiple project spaces, has favored a pulviscular articulation also in the sectors adjacent to design, such as, undoubtedly, drawing. [read more]